Do Uncertainties in US Affect Bitcoin Returns? Evidence from Time Series Analysis - Miba'am, Benjamin Walwai; Gungor, Hasan (Springer, 2025)
The study attempts to add to the existing literature on the relationship between uncertainties and Bitcoin by determining the direction of the relationship between Economic Policy Uncertainty (EPU), Geopolitical Risk (GPR), Political Risk (PR) and Bitcoin returns. This is to ascertain if Bitcoin hedges and is a safe haven asset against uncertainties. We employed the use of Ordinary Least Square (OLS), Autoregressive Distributive Lag (ARDL) and Quantile Regression (QR) to achieve the research objective. Having discovered the existence of structural breaks after conducting the Zivot-Andrews unit root for structural breaks, the analysis was divided into full sample period, first sub-period and the second sub-period. Findings show that EPU, GPR and PR hedge and play the role of safe haven against uncertainties in the United States (US). We found that EPU exerts positive influence against Bitcoin returns while GPR and PR negatively influence Bitcoin returns. The result further shows that Bitcoin returns hedges against EPU in the lower and middle quantiles while Bitcoin returns hedges against PR only in the lower quantile. The study therefore concludes that uncertainty and risk in the US influence bitcoin returns. It supports the hedging ability and safe haven properties of bitcoin, emphasising that bitcoin returns react more to EPU US than GPR US and PR US, therefore recommending investment experts and financial analysts focus more on EPU US than GPR US and PR US.
Keywords: Bitcoin Returns; Economic Policy Uncertainty; Geopolitical Risk; Political Risk; Uncertainties; C22; G01; G11; G15; O33